Mating-type genes and sexual potential in the ascomycete genera Aspergillus and Penicillium - Eagle, C. (2009)
Mating-type and other ‘sex-related’ genes in the filamentous ascomcyete genera Aspergillus and Penicillium, were examined to investigate the potential sexual capacity of supposedly asexual species and also the possible evolutionary route and ancestry of mating strategy and mating-type genes.